The Screen of a Phage Display Library Identifies a Peptide That Binds to the Surface of Trypanosoma cruzi Trypomastigotes and Impairs Their Infection of Mammalian Cells - de Paula, Jéssica I.; Lopes-Torres, Eduardo J.; Jacobs-Lorena, Marcelo; Paes, Marcia Cristina; Cha, Sung-Jae (Frontiers in Microbiology, 2022)
Background Chagas is a neglected tropical disease caused by the protozoan parasite Trypanosoma cruzi. On the order of seven million people are infected worldwide and current therapies are limited, highlighting the urgent need for new interventions. T. cruzi trypomastigotes can infect a variety of mammalian cells, recognition and adhesion to the host cell being critical for parasite entry. This study focuses on trypomastigote surface ligands involved in cell invasion. Methods Three selection rounds of a phage peptide display library for isolation of phages that bind to trypomastigotes, resulted in the identification of the N3 dodecapeptide. N3 peptide binding to T. cruzi developmental forms (trypomastigotes, amastigotes and epimastigotes) was evaluated by flow cytometry and immunofluorescence assays. Parasite invasion of Vero cells was assessed by flow cytometry and immunofluorescence assays. Results Phage display screening identified the N3 peptide that binds preferentially to the surface of the trypomastigote and amastigote infective forms as opposed to non-infective epimastigotes. Importantly, the N3 peptide, but not a control scrambled peptide, inhibits trypomastigote invasion of Vero cells by 50%. Conclusion The N3 peptide specifically binds to T. cruzi, and by doing so, inhibits Vero cell infection. Follow-up studies will identify the molecule on the parasite surface to which the N3 peptide binds. This putative T. cruzi ligand may advance chemotherapy design and vaccine development.